SAMORZĄD TERYTORIALNY JAKO INSTYTUCJA SPOŁECZEŃSTWA OBYWATELSKIEGO - Rieres, Leon (Wydział Prawa i Administracji UAM, 2006)
The community of people living in a certain territory and related to one another by common interests has a civic character if the identity of that community is guaranteed. Further, the identity of a civic community is expressed by its independence. The independence of a local organ should be guaranteed by appropriate legislative acts, or else it is ficitious in law and members of the community will loose their feeling of belonging to the community. Consequently, they may also start loosing confidence in the State and feel discouraged to participate in public life. However, certain pathologies that are sometimes observed in the activities in organs of local authorities may serve as an argument against such self governing bodies. Certain legal solutions implemented to prevent undesired behaviour of public officers might serve as a certain remedy, which will not however, satisfactorily substitute ethical principles upon which their attitudes should be based.
LOCAL AUTHORITIES AS AN INSTITUTION OF A CIVIC SOCIETY